A=3Ca+b

Rewrite the equation as 3Ca+b=A.

3Ca+b=A

Multiply each term by a+b and simplify.

Multiply each term in 3Ca+b=A by a+b.

3Ca+b⋅(a+b)=A⋅(a+b)

Cancel the common factor of a+b.

Cancel the common factor.

3Ca+b⋅(a+b)=A⋅(a+b)

Rewrite the expression.

3C=A⋅(a+b)

3C=A⋅(a+b)

Apply the distributive property.

3C=Aa+Ab

3C=Aa+Ab

Rewrite the equation as Aa+Ab=3C.

Aa+Ab=3C

Subtract Aa from both sides of the equation.

Ab=3C-Aa

Divide each term by A and simplify.

Divide each term in Ab=3C-Aa by A.

AbA=3CA+-AaA

Cancel the common factor of A.

Cancel the common factor.

AbA=3CA+-AaA

Divide b by 1.

b=3CA+-AaA

b=3CA+-AaA

Simplify each term.

Cancel the common factor of A.

Cancel the common factor.

b=3CA+-AaA

Divide -1a by 1.

b=3CA-1a

b=3CA-1a

Rewrite -1a as -a.

b=3CA-a

b=3CA-a

b=3CA-a

b=3CA-a

Solve for b A=(3C)/(a+b)